Challenges to Public Management and Reaction Strategies in the Modern Capitalist Society - Bi, Guojie (International Journal of Social Sciences and Public Administration, 2025)
This paper analyzes the challenges encountered in modern capitalist societies and explores plausible reactions to these problems. Public administration must deal with the complex issues resulting from globalization, technological advancements, and demographic shifts, which generate obstacles to governance. The study highlights the theoretical and practical significance of comprehending these challenges to elevate efficiency in public administration. Through a combination of literature review and qualitative analysis, the study investigates the fundamental causes of these challenges like economic inequalities, governance limitations, and the widening social division, proposing adaptive strategies such as adopting digital governance, inclusive policy-making, and strengthened accountability. These strategies aim to foster equitable, sustainable, and efficient public management, and contribute to social stability and prosperity.